Rights of Component in the Republic of Turkey - Rahman, Shalaw Sabah Abdul; Saleh, Saleh Abdullah (Journal of Legal and Political Studies, 2022)
The issue of minority rights is of great importance in the contemporary world, particularly in states where there are multiple minorities, and sometimes these diversity of nationalities and ethnic differences pose a challenge and disruption to their stability and national security, and at other times one of the reasons for their excellence and rich social structure, national minorities have collective political, civil and cultural demands such as the right to self- administration and education in the mother tongue Participation in the political process, which involves its own constitutional organization, is formulated in a way that creates harmony among the components of this society. With regard to the position of the constitutional founder in Turkish constitutions, around rights of an intelligent society, we find different positions, some of which are geared towards highlighting Turkish nationalism and the Turkish nation and denying the existence rights and freedoms for all citizens of Turkey As for the amendments to the Constitution of the Republic of Turkey of 1982, which are reluctant to play the role of the military in interfering in political and constitutional life, although there is no amendment to any article on the rights of national minorities, they have a role to play in giving a simple bit of minority rights
Keywords: minority rights; contemporary world; diversity of nationalities; social structure; Constitution of the Republic of Turkey of 1982